Person-centred prescribing: an imperative in the face of the clinical complexity of ageing - Ana Julia, Ana Julia (Horizonte Sanitario, 2025)
Person-centred prescribing is examined as a response to the challenges presented by population ageing. Medicines, which are the most commonly used health technology, face increasing problems of adequacy in contexts of multimorbidity and advanced chronicity. The complexity of drug use involves multiple factors, from production to consumption, and the concepts of appropriate prescribing are dynamic and vary according to the life trajectory. In the case of older people, ageing with multimorbidity results in polypharmacy (defined as the use of five or more chronic drugs) and poor therapeutic adequacy, especially in frail and end-of-life individuals.Traditional clinical guidelines are insufficient for this heterogeneous population, which is often excluded from studies. Although technical tools are available to assess anticholinergic burden, interactions, and inappropriate prescriptions, a structured model that integrates them is needed. The patient-centred prescribing (PCP) model suggests a comprehensive approach through three assessments: person-centred (assessing adherence and agreeing on therapeutic objectives), diagnosis-centred (identifying health problems and deprescribing strategies), and drug-centred (re-evaluating indications and simplifying guidelines).This multidimensional and biopsychosocial approach, carried out by interdisciplinary teams, incorporates the patient's preferences and reduces inappropriate prescribing.  Keyword:  Drug Prescriptions; Aging; Patient-Centered Care.